Better drip than flood: Reaping the benefits of efficient irrigation - Ignaciuk, Ada; Mason-D’Croz, Daniel; Islam, Shahnila (Wiley, 2015)
By 2050, the global demand for land and water for agricultural use is projected to increase. Climate change is likely to affect agricultural production through increased temperatures as well as through altered precipitation patterns, which are likely to increase water deficiency in many regions. Measures seeking to increase water efficiency and resilience of the agricultural sector to climate change will therefore be critical. The benefits of more efficient irrigation systems are especially apparent in regions already suffering from water shortages, such as the Mediterranean Basin, or those that are likely to suffer in the future, such as the Southern Cone of South America. However, unless incentives for saving water are in place, farmers may decide to expand their area of irrigated land, or to switch to water‐intensive, higher‐value commodities. Extending irrigation generally constitutes mixed blessings. In regions experiencing water deficits, extending irrigation may lead to greater water stress on irrigated agriculture. Meanwhile, when applied globally and governed carefully, efficient irrigation techniques and extending irrigation can yield overall increases in agricultural production that can reduce agricultural commodity prices. Stimulating water‐efficient irrigation systems may thus prove crucial in improving farmers' resilience over time, though such measures should be supported by other economic instruments such as water pricing or water trading, where necessary.